Determinants of dermal exposure among Nicaraguan subsistence farmers during pesticide applications with backpack sprayers - Blanco, Luis (2005)
Identification of pesticide exposure determinants has become an issue in explaining exposure variability and improving control measures. Most studies have been conducted in industrialized countries. The aim of this study was to identify relevant dermal exposure determinants among Nicaraguan subsistence farmers. About the methods, Field data on possible determinants were collected during 32 pesticide applications through observation and supplementary videorecording. A multistep reduction strategy brought down the 110 potential exposure determinants to 27 variables, which were grouped as worksite, spray equipment, working practices, clothing or hygiene practices related. Dermal exposure was quantified with a modification of Fenske’s visual scoring method. Multivariate linear regression modeling within groups and across groups was performed. Among the main results are that in the within-group analyses, work practices, spray equipment and worksite related determinants explained 52, 33 and 25% of the exposure variability, respectively. Clothing and hygiene practices were weaker determinants and did not always reduce the exposure. The final model included determinants from all groups except hygiene practices and explained 69% of the exposure variability. A less restricted model increased the explained variability to 75%. Several novel determinants were identified, including spraying on a muddy terrain, dew on plants, sealing the tank lid with a cloth and wiping sweat from the face. Lastly in conclusions this study showed that a combination of observation and visual scoring techniques can provide valuable information on determinants of pesticide exposure and affected body parts under developing country conditions. The results could be used to develop jobspecific questionnaires and to design training and preventive programs.